World Economic Outlook, April 2018 : Cyclical Upswing, Structural Change. (World Economic Outlook; World Economic Outlook ;, 2018)
The upswing in global investment and trade continued in the second half of 2017. At 3.8 percent, global growth in 2017 was the fastest since 2011. With financial conditions still supportive, global growth is expected to tick up to a 3.9 percent rate in both 2018 and 2019. Advanced economies will grow faster than potential this year and next; euro area economies are set to narrow excess capacity with support from accommodative monetary policy, and expansionary fiscal policy will drive the US economy above full employment. Aggregate growth in emerging market and developing economies is projected to firm further, with continued strong growth in emerging Asia and Europe and a modest upswing in commodity exporters after three years of weak performance. Global growth, however, is projected to soften beyond the next couple of years, with most advanced economies likely returning to potential growth rates well below precrisis averages. Growth is projected to remain subpar in several emerging market and developing economies, including in some commodity exporters that continue to face substantial fiscal consolidation needs. Beyond the next few quarters risks clearly lean to the downside. The current recovery offers a window of opportunity to advance policies and reforms that secure the current upswing and raise medium-term growth to the benefit of all.